1996
DOI: 10.1093/infdis/174.2.268
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Immunogenicity, and Protective Efficacy of One and Three Doses of the Tetravalent Rhesus Rotavirus Vaccine in Infants in Lima, Peru

Abstract: An oral rhesus-human rotavirus tetravalent (RRV-TV) vaccine (10(4) pfu of rhesus rotavirus [type G3] and of 3 human-rhesus reassortants [G1, G2, and G4]) was evaluated in a field trial in Lima, Peru. At 2, 3, and 4 months of age, infants received either a dose of RRV-TV, an initial dose of vaccine followed by a dose of placebo at 3 and 4 months, or a dose of placebo. Rotavirus-specific IgA responses were detected by ELISA in 75% of the three-dose vaccine group, 59% of the one-dose vaccine group (P = .05), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
6

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 42 publications
1
60
0
6
Order By: Relevance
“…Interference by maternal antibodies may explain the need for two or more rotavirus infections (symptomatic or asymptomatic) to provide protection against moderate to severe diarrhoea in Mexican children (Velazquez et al, 1996). Lanata et al (1996) have reported that in Peru, three doses of oral rotavirus vaccine (4i10% p.f.u. per dose) did not increase vaccine efficacy compared with one dose (efficacies of 35-66 % against severe diarrhoea), whereas Perez-Schael et al (1997) found in Venezuela that three doses of 4i10& p.f.u.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interference by maternal antibodies may explain the need for two or more rotavirus infections (symptomatic or asymptomatic) to provide protection against moderate to severe diarrhoea in Mexican children (Velazquez et al, 1996). Lanata et al (1996) have reported that in Peru, three doses of oral rotavirus vaccine (4i10% p.f.u. per dose) did not increase vaccine efficacy compared with one dose (efficacies of 35-66 % against severe diarrhoea), whereas Perez-Schael et al (1997) found in Venezuela that three doses of 4i10& p.f.u.…”
Section: Discussionmentioning
confidence: 99%
“…Several oral vaccines have been developed based on heterologous host rotaviruses, attenuated human rotavirus (HRV) and human-animal rotavirus reassortants. A tetravalent human-rhesus reassortant rotavirus vaccine was effective in reducing rotavirus-induced diarrhoea in trials in the USA and Finland (Bernstein et al, 1995 ;Joensuu et al, 1997 ;Rennels et al, 1996 ;Ward et al, 1997) but was less effective in trials in some developing countries (Lanata et al, 1996 ;Linhares et al, 1996). The reduced efficacy may reflect the lower vaccine dose used in these latter trials (4i10% vs 4i10& p.f.u.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first oral RV vaccine (Rotashield) was clinically effective in five global trials (12,15,18,20). However, it was withdrawn because of possible causative relationship to intussusception in infants (14).…”
mentioning
confidence: 99%